Kaiju no. 8. 7 - Matsumoto, Naoya, 1982- (Shonen Jump manga., 2023)
"Kaiju No. 9 shows up to steal the power of Kaiju No. 2, wielded by Isao Shinomiya, director general of the Defense Force. At the end of the deadly battle, Isao manages to get No. 9 on the ropes, but he ends up exhausting all his strength, allowing the kaiju to steal No. 2's power. With Isao defeated, No. 9 fuses with the director general and takes on Kafka, Kikoru, and Narumi! Will they be able to defeat No. 9 and save their fearless leader?!"--